Evaluación de parámetros de calidad de la lana de oveja 4m (Marin Magellan Meat Merino) en el núcleo genético de Yanahurco En El Cantón Saquisilí Provincia De Cotopaxi. - Suntasig Suntasig, Mónica Mireya (2020)
The investigative Project is developed in the province Cotopaxi, canton Saquisili about sheep Genetic Nucleus of Yanahurco, It has with 450 breed sheep 4M. The main object was evaluate the parameters which determine the quality of sheep wool of this breed after of its adaptation in this town, Initially, a selection of the animals was made by creating two study groups taking into account their age and sex (male and female). Accordingly, it was sought to determine if age and sex are factors that directly enter into the parameters of the quality sheep wool. Each animal selected for the investigation had a distinctive that served as reference and precise data for the sampling which were obtained and evaluated within the stableshment; Preliminary data were estimated which were qualitatively evaluated, subsequently 25 g samples were collected. fiber, from the right middle rib of each of the sheep evaluated, these were then placed in individually labeled polyethylene bags and transferred to the laboratories for their respective analysis using an opto-mechanical mechometer called FIBRELUX with the help of this equipment, the fineness, length, waving between other characteristics, the results obtained by the equipment obtain a reliability is assessed, is so that the results obtained were great help in the time to examine the obtained result and compare themselves with references data, it was proceeded to examine stadistically by means of a variance analysis using a factorial arrangement A*B design with a composite database for 36 wool samples. according to the analysis carried out, it was found that, there is an effect of age and sex within the measures of fineness and length of wick so that the greatest difference is found in the parameter of fineness. This research will serve to continue with the genetic improvement plan within the province; the results obtained were respectively analyzed and exposed to the different beneficiaries of the project providing records that will later serve research.